Polymer viscoelasticity stress and strain in practice - Riande, Evaristo (Plastics engineering (Marcel Dekker, Inc.), 2000)
Showcasing vital engineering applications to transient and dynamic pertubations of macromolecular materials, structural recovery's role in mechanical responses in the glassy state, and viscoelastic parameters that condition the non-Newtonian behaviour of polymers, this work presents a systematic account of the responses of macromolecular materials to mechanical force fields. It focuses on the most important features of the linear stress-strain relationships for ideal solids and liquids.